2017
DOI: 10.1186/s12967-017-1331-4
|View full text |Cite
|
Sign up to set email alerts
|

DCE-MRI of patient-derived xenograft models of uterine cervix carcinoma: associations with parameters of the tumor microenvironment

Abstract: BackgroundAbnormalities in the tumor microenvironment are associated with resistance to treatment, aggressive growth, and poor clinical outcome in patients with advanced cervical cancer. The potential of dynamic contrast-enhanced (DCE) MRI to assess the microvascular density (MVD), interstitial fluid pressure (IFP), and hypoxic fraction of patient-derived cervical cancer xenografts was investigated in the present study.MethodsFour patient-derived xenograft (PDX) models of squamous cell carcinoma of the uterine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…DCE-MRI has been specifically applied to the detection of hypoxia in various tumors in an attempt to correlate the results with the pO 2 levels in tissue. This goal has been achieved with unequal results in different types of cancers and a direct correlation between Eppendorf probe results (Cooper et al, 2000 ) and pimoinidazole staining (Hauge et al, 2017 ) has been observed in cervical cancer or prostate cancer (Hoskin et al, 2007 ). However, this correlation with pimoinidazole staining has not been fully clarified thus far in other cases, such as at HNSCC (Newbold et al, 2009 ; Donaldson et al, 2011 ) or [ 18 F]-FMISO uptake in glioblastomas (Swanson et al, 2009 ).…”
Section: Preclinical and Clinical Imaging Of Hypoxiamentioning
confidence: 99%
“…DCE-MRI has been specifically applied to the detection of hypoxia in various tumors in an attempt to correlate the results with the pO 2 levels in tissue. This goal has been achieved with unequal results in different types of cancers and a direct correlation between Eppendorf probe results (Cooper et al, 2000 ) and pimoinidazole staining (Hauge et al, 2017 ) has been observed in cervical cancer or prostate cancer (Hoskin et al, 2007 ). However, this correlation with pimoinidazole staining has not been fully clarified thus far in other cases, such as at HNSCC (Newbold et al, 2009 ; Donaldson et al, 2011 ) or [ 18 F]-FMISO uptake in glioblastomas (Swanson et al, 2009 ).…”
Section: Preclinical and Clinical Imaging Of Hypoxiamentioning
confidence: 99%
“…Clinical investigations have revealed that low K trans values reflect poor vascularization and blood supply in LACC [9,27,28]. Preclinical studies of human cervical carcinoma xenografts have shown strong inverse correlations between median K trans and fraction of hypoxic tumor tissue, regardless of whether radiobiological or pimonidazole-based immunohistochemical assays were used to quantify tumor hypoxia [5,[29][30][31]. Therefore, it is reasonable to assume that RV-K trans mirrors the hypoxic subvolume in tumors of the uterine cervix.…”
Section: Discussionmentioning
confidence: 99%
“…9 When the K trans value is lower, it is more likely to have poor blood flow and/or low vessel permeability within the tumor area, and thus tumor hypoxia and high HIF-1α expression occurs. 21 Similarly, Hauge et al 22 investigated the potential value of DCE-MRI to assess tumor hypoxia on the basis of xenograft models of cervical carcinoma, and found that, compared with V e , K trans had a higher correlation with the hypoxia fraction for cervical carcinoma. FIGURE 2: DCE perfusion MRI and IVIM DWI in early cervical carcinoma that had low HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%